Eventful cities : cultural management and urban revitalisation - Richards, Greg, ....-; Palmer, Robert, 1947- (Amsterdam : Butterworth-Heinemann, 2010)
Processes of globalisation, economic restructuring and urban redevelopment have placed events at the centre of strategies for change in cities. Events offer the potential to achieve economic, social, cultural and environmental outcomes within broader urban development strategies. This volume: * Analyses the process of cultural event development, management and marketing and links these processes to their wider cultural, social and economic context * Provides a unique blend of practical and academic analysis, with a selection of major events and festivals in cities where eventfulness has been an important element of development strategy * Examines the reasons why different stakeholders should collaborate, as well as the reasons why cities succeed or fail to develop events and become eventful Eventful Cities: cultural management and urban revitalisation evaluates theoretical perspectives and links theory and practice through case studies of cities and events across the world. Critical success factors are identified which can help to guide cities and regions to develop event strategies. This book is essential reading for any undergraduate or graduate student and all practitioners and policy-makers involved in event management, cultural management, arts administration, urban studies, cultural studies and tourism.
Includes bibliographical references and index.
Keywords: City promotion -- Management -- Europe -- Case studies; City promotion -- Management; Cultuurmanagement; Evenementen; Special events -- Management -- Europe -- Case studies; Special events -- Management; Stadsvernieuwing; Steden; Urban economics; Urban renewal -- Europe -- Case studies; Urban renewal